2017
DOI: 10.1016/j.cub.2017.09.067
|View full text |Cite
|
Sign up to set email alerts
|

The Diversity, Structure, and Function of Heritable Adaptive Immunity Sequences in the Aedes aegypti Genome

Abstract: SUMMARY The Aedes aegypti mosquito transmits arboviruses including dengue, chikungunya and Zika virus. Understanding the mechanisms underlying mosquito immunity could provide new tools to control arbovirus spread. Insects exploit two different RNAi pathways to combat viral and transposon infection: short-interfering RNA (siRNAs) and PIWI-interacting RNAs (piRNAs) [1, 2]. Endogenous viral elements (EVEs) are sequences from non-retroviral RNA viruses that are inserted into the mosquito genome and act as template… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
242
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(264 citation statements)
references
References 58 publications
22
242
0
Order By: Relevance
“…We then created a custom database comprised of all single-stranded DNA (ssDNA) and nonretroviral RNA virus protein sequences available in GenBank and used this database to identify putative EVEs genome wide in each arthropod genome via BLASTx. As reported previously, we found that a large number of putative EVEs could not be unambiguously classified as viral due to homology with eukaryotic, bacterial, or archaeal sequences (14). We removed the majority of putative EVEs that were homologous to eukaryotic sequences via reverse BLAST searches against the D. melanogaster proteome.…”
Section: Resultsmentioning
confidence: 99%
“…We then created a custom database comprised of all single-stranded DNA (ssDNA) and nonretroviral RNA virus protein sequences available in GenBank and used this database to identify putative EVEs genome wide in each arthropod genome via BLASTx. As reported previously, we found that a large number of putative EVEs could not be unambiguously classified as viral due to homology with eukaryotic, bacterial, or archaeal sequences (14). We removed the majority of putative EVEs that were homologous to eukaryotic sequences via reverse BLAST searches against the D. melanogaster proteome.…”
Section: Resultsmentioning
confidence: 99%
“…BHK cells (Aguirre et al, 2017) (unsexed) were cultured in minimal essential medium α (MEM α) (Thermo Fisher), supplemented with 10% FBS (Thermo Fisher), GlutaMAX (Thermo Fisher), 100 U/mL penicillin (Thermo Fisher), 100 μg/mL streptomycin (Thermo Fisher), and 10 mM HEPES (Thermo Fisher). Aag2 cells (Whitfield et al, 2017) (unknown gender) were culture in Schneider’s Drosophila medium (Invitrogen) supplemented with 10% FBS (Invitrogen), 1% pen/strep and 1% non-essential amino acids. C6/36 cells (Alvarez et al, 2005) (unknown gender) were cultured in L-15 medium supplemented with 10% FBS (Invitrogen), 1% pen/strep and 1% non-essential amino acids.…”
Section: Star Methodsmentioning
confidence: 99%
“…We were ultimately interested in studying the potential impact of persistent PCLV infection on acute superinfection with arboviruses in our Aag2-derived clonal cell lines, and therefore first investigated whether sequences derived from PCLV specifically are also integrated into the parental Aag2 cell genome. We performed a BLASTn search against the Aag2 reference genome [70] using our previously published full-length genome sequences for the PCLV known to infect the parental Aag2 cell line [57]. We did not identify any statistically significant (E-value <10 −5 ) PCLV-derived sequences from any of the three viral genome segments (L, M, S) in the Aag2 reference genome sequence.…”
Section: Resultsmentioning
confidence: 99%
“…Our previously published full-length PCLV genome sequences from Aag2 cells (Genbank accession numbers KU936055, KU936056 and KU936057) [57] were searched against the Aag2 cell reference genome [70] using the BLAST function at vectorbase.org [71].…”
Section: Methodsmentioning
confidence: 99%